PENDIDIKAN ANAK LERENG PEGUNUNGAN ARGOPURO: EDUCATION FOR CHILDREN ON THE SLOPES OF MOUNT ARGOPURO - Ahmad Royani ,Mukni'ah (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2018)
This study focuses first on the perspective of farm workers on children's education, and second on the alternative education chosen by farm workers for their children's education. This study uses a descriptive qualitative research method with a case study approach on farm worker families. The subjects of this study are parents (fathers and mothers) and children from farm worker families. The research setting is Wonosari Village, Grujugan Subdistrict, Bondowoso, on the slopes of Mount Argopuro. The results of this study explain that the perspective of farm workers on children's education has several characteristics. The research setting was in Wonosari Village, Grujugan Bondowoso District, at the foot of Mount Argopuro. The results of this study explain that the perspectives of farm workers on children's education include several things, namely: 1) strengthening children's morals, 2) strengthening the value of independence in children, 3) improving social status in the community, and 4) education is also seen as a means of social mobility. Meanwhile, the alternative education pursued by the children of farming communities in Wonosari Village is formal education and religious education. Islamic boarding schools are used as an alternative education option for farming communities in Wonosari Village when parents are unable to provide higher formal education for their children. Penelitian ini di fokuskan pertama pada presefektif buruh tani tentang pendidikan anak, kedua difokuskan pada alternatif pendidikan yang dipilih oleh buruh tani untuk pendidikan anak. Penelitian ini menggunakan jenis penelitian deskriptif kualitatif dengan pendekatan studi kasus pada keluarga buruh tani. Subjek penelitian ini adalah orangtua (bapak dan ibu) dan anak dari keluarga buruh tani. Setting penelitian ini dilakukan di Desa Wonosari Kecamatan Grujugan Bondowoso di ereng gunug Argopuro. Dari hasil penelitian ini dijelaskan bahwa presfektif pendidikan buruh tani tentang pendidikan anak ada beberapa hal yaitu; 1) sebagai penguatan akhlak anak, 2) Pengauatan nilai kemandirian anak, 3) meningkatkan status sosial di masyarakat dan 4) pendidikan juga dipandang sebagai mobilitas sosial. Sedangkan alternatif pendidikan yang ditempuh anak-anak masyarakat petani di Desa Wonosari adalah pendidikan formal dan pendidikan agama. Pondok Pesantren dijadikan sebagai pendidikan alternatif pilihan masyarakat petani di Desa Wonosari ketika orang tua sudah tidak mampu memberikan pendidikan formal yang lebih tinggi kepada anak-anak mereka.